Weighty issue. (December 2021) - Calverd, Alan; Watson, Tim
Abstract : A response to Nick England's letter "Going in circles" in which he discusses the change from teaching centrifugal force to teaching centripetal force, and the definition of weight being changed from the reaction force felt from the floor to the pull of gravity on an object.